Analisis Kinerja Keuangan Perusahaan Terhadap Income Smoothing - Anggraini, Yunita; Kusumawati, Fariyana (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2024)
This purpose of this research is to determine the effect of profitability, laverage, company size, and company age on income smoothing. The research design used in this study is quantitative. This research was conducted on consumer goods sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Sampling method purposive sampling a sample of 30 companies oe 120 was obtained annual report who meet the sample criteria during the research period. The data analysis method used is multiple linier regression analysis using SPSS version 23. The results in this study indicate that profitability and laverage has no effect on income smoothing, while the company size has a positive effect on income smoothing, and company age has a negative effect on income smoothing.